A Rare Fatal Case of Cardiac Perforation During Cardioverter-Defibrillator Implantation - Rosato, Enrica; Bonelli, Martina; D’Ovidio, Cristian (Archives of Clinical and Medical Case Reports, 2020)
Right ventricular perforation is a rare but fatal complication during implantation and removal of cardiac devices. The causes of such an event are not well defined, although among the various factors involved, the thickness of the ventricular wall and the force exerted by the operator appear to be important. We report here a case of fatal cardiac resynchronization therapy with defibrillation in a patient without apparent predictive factors for perforation. This case highlights the importance of revisiting the diagnostic pathways before introduction of a cardiac device, and of further studies on the predictive factors, to avoid a complication being considered as a surgical error.